The Validity of Notary Public Deeds in the Capital Market During a Vacuum of License Due to the Retroactive Cancellation of Registration Certificates by the Financial Services Authority - Tanaya, Velliana; Hasianatama, Tri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The increasingly significant Indonesian capital market demands a vital role from supporting professions like Capital Market Notaries to ensure legal certainty and compliance. The Financial Services Authority Regulation (POJK) Number 67/OJK.04/2017 mandates the re-registration of the Registered Certificate (STTD), but its implementation triggered an administrative crisis that led to the cancellation of 1066 Notary STTDs, creating a period of